The enlargement of the European Union – Poland’s example. Between unity and diversity - Czachór, Zbigniew (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
The history of Poland’s integration activities, undertaken both before and after joining the EU, has featured several attempts to demonstrate its desire to become an independent entity in the internal EU game of the interests of other EU countries and institutions. This has been the case, since Poland’s interests have not always been compatible with the interests of the other actors of integration. For instance, Poland has opposed the scenario of the faster development of countries forming the ‘hard core’ of the EU. On the other hand, Poland still supports the universal postulate of making Europe a continent of democracy, freedom, peace and progress. The European Union has remained the guar - antee that the lines that divide Europe will be erased and stable and consistent development ensured. Therefore, the author believes that Europe (the European Union) has no alternative, and will have to opt for a universalist-and-particular synthesis of unity in multiplicity, and unity in diversity, which enriches and develops but does not divide countries. First and foremost, this synthesis emphasizes the common good while not losing sight of (abandoning) the individual good.

Polska kilka razy w swej historii aktywności integracyjnej przed i po przystąpieniu do UE podjęła próbę zademonstrowania pozostałym krajom UE i unijnym instytucjom, że chce być samodzielnym podmiotem wewnątrz-unijnej gry interesów. Tym bardziej, że nie zawsze interesy Polski są zgodne z interesami pozostałych aktorów integracji. Na przykład sprzeciwiamy się postulatowi szybszego rozwoju krajów należących do „twardego jądra” UE. Z drugiej strony Polsce nadal bliskie jest uniwersalistyczne przesłanie, które brzmi: naszym wspólnym życzeniem jest uczynienie Europy kontynentem demokracji, wolności, pokoju i postępu. Unia pozostaje dla Polski nadal gwarantem redukowania linii podziału w Europie i popierania stabilności i pomyślnego rozwoju. Z uwagi na powyższe, zdaniem autora nie ma innego wyjścia, Europa (UE) musi postawić na uniwersalistyczno-partykularną syntezę jedności w wielości oraz jedności w różnorodności, która wzbogaca i rozwija, ale nie rozbija. A przede wszystkim eksponuje dobro wspólne bez zaniku (zatracania) dobra indywidualnego.
Rozszerzenie Unii Europejskiej – przykład Polski. Między jednością a różnorodnością
Keywords: integration activity; działania integracyjne; enlargement; rozszerzenie; interests; interesy; common good; dobro wspólne; accession; przystąpienie